2015
DOI: 10.1007/s13353-015-0320-7
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing as a powerful tool in searching for genes influencing health and performance traits of horses

Abstract: RNA sequencing (RNA-seq) by next-generation technology is a powerful tool which creates new possibilities in whole-transcriptome analysis. In recent years, with the use of the RNA-seq method, several studies expanded transcriptional gene profiles to understand interactions between genotype and phenotype, supremely contributing to the field of equine biology. To date, in horses, massive parallel sequencing of cDNA has been successfully used to identify and quantify mRNA levels in several normal tissues, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…RNA‐seq has been used in physiologic studies to characterize the equine transcriptome (Stefaniuk & Ropka‐Molik, ) and alterations in the transcriptome of Holstein milk over a 250‐day period (Wickramasinghe, Rincon, Islas‐Trejo, & Medrano, ). Pathological conditions such as changes in the immune response of sheep to Fasciola hepatica (Rojas et al., ) and pathway analysis of canine lymphoma (Mooney et al., ) highlight the use of RNA‐seq in monitoring alterations in the transcriptome in response to disease states.…”
Section: Introductionmentioning
confidence: 99%
“…RNA‐seq has been used in physiologic studies to characterize the equine transcriptome (Stefaniuk & Ropka‐Molik, ) and alterations in the transcriptome of Holstein milk over a 250‐day period (Wickramasinghe, Rincon, Islas‐Trejo, & Medrano, ). Pathological conditions such as changes in the immune response of sheep to Fasciola hepatica (Rojas et al., ) and pathway analysis of canine lymphoma (Mooney et al., ) highlight the use of RNA‐seq in monitoring alterations in the transcriptome in response to disease states.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, transcriptome sequencing analysis technology has been extensively applied in studying the molecular regulation mechanisms related with growth, metabolism, disease resistance, and so on quantitative traits in agricultural animals [31][32][33][34][35]. In the field of chicken reproductive performance regulation-related research, Ayers et al studied the mechanism of sex differentiation in chicken using the RNA-seq technology and found that most of the differentially expressed genes in different genders come from autosomal rather than sex-chromosome linkage, many of which are novel genes for sexual differentiation, such as CAPN5, GPR56, and FGFR3 [36].…”
Section: Transcriptome Sequencing (Rna-seq) Is a Powerful Tool To Reveal The Regulatory Network And Molecular Mechanisms Of Quantitative mentioning
confidence: 99%
“…Recent advances in next-generation sequencing (NGS) technology have provided researchers with unprecedented tools to increase the discovery of genetic variation associated with traits of economic importance in animals (Petersen et al 2013;Crisà et al 2016;Stefaniuk et al 2016;Purfield et al 2017). But this method was rarely reported to be used to study the milk traits of horse.…”
Section: Introductionmentioning
confidence: 99%